Evaluation of Group Consulting on Pregnancy Anxiety: A Randomized Clinical Trial - Dayhimi, Marjaneh; Kariman, Nourossadat; Shams, Jamal; Akbarzadeh Baghban, Alireza (Advances in Nursing & Midwifery, 2020)
Introduction: Anxiety is a disorder of mental health in pregnant women reported by 20 percent of health care providers and is accompanied by adverse pregnancy outcomes. This study aimed to determine the effect of obstetric counseling on the anxiety of pregnant women. Methods: In this randomized, double-blind controlled trial, 90 pregnant women attending to Sheibani Health Care Center in Tehran aging from 18 to 35 years old and with a gestational age of 8 to 18 weeks were evaluated first pregnancy. They were randomly assigned to counseling (group counseling with routine perinatal care) and control (only routine perinatal care) groups. The group counseling was designed according to different needs of pregnancy for five sessions in five weeks (a duration of 60 to 90 minutes for each session). The questionnaires of demographic information, Beck Depression, and Spielberg spiel Berger State-trait anxiety were used. The data analysis was performed by SPSS software version 13 using parametric and non-parametric tests. Results: According to the results, there was a significant difference between post-intervention scores in state anxiety (P = 0.014); however, there was no significant difference in trait anxiety (P = 0.19). Also, the changes in trait anxiety were more in the consoling group compared with the control group (P = 0.002), which is also seen for the state anxiety group (P = 0.0001). Conclusions: It is concluded from this study that group counseling is effective in the reduction of state anxiety and trait anxiety in pregnant women.